1992
DOI: 10.3168/jds.s0022-0302(92)78130-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raw Pea Flour on Nutrient Digestibility and Immune Responses in the Preruminant Calf

Abstract: Two milk substitute diets for which the protein was provided either exclusively by skim milk powder (control) or partially (34%) by dehulled raw pea flour were given for 2 and 4 wk, respectively, to five preruminant calves, each fitted with a reentrant ileocecal cannula. Ileal apparent digestibility was lower with the pea diet during wk 1 than with the control diet. Four of the cannulated calves exhibited significant intolerance to the pea diet, resulting in lower digestibility during wk 4. In contrast, fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
5
19
0
1
Order By: Relevance
“…Proteins from feeds and digesta were extracted in borate buffer as described by Bush et al (1992). Immunometric ELISA's were set up for each purified soy globulin utilizing modifications of procedures described by Heppell (1985) and Heppell et al (1987 Values were expressed as native globulin equivalents.…”
Section: Elisa Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins from feeds and digesta were extracted in borate buffer as described by Bush et al (1992). Immunometric ELISA's were set up for each purified soy globulin utilizing modifications of procedures described by Heppell (1985) and Heppell et al (1987 Values were expressed as native globulin equivalents.…”
Section: Elisa Assaysmentioning
confidence: 99%
“…The ELISA approach seems to be inappropriate for prediction of intestinal flow of dietarv oroteins in ruminants. Indeed, antibodiei riised against the native globulins cross-react with some but not all corresponding subunits (review by Brooks and Morr (1985)) and recognize fairly large globulin fractions in digesta (Bush et al 1992 (Spencer et al 1988) and to satisfactorily predict protein degradability (Romagnolo et al 1990 A possible contribution of the immune system to local (gut) unresponsiveness after weaning cannot be excluded.…”
Section: Protein and Soybean Globulin Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been shown that the B protein has negligible measurable sulfur amino acids, while the a protein contains less than I% and the 7 protein contains approximately 2% (Blagrove and Gillespie 1975). Doyle et al (1992) Bush et al (1992 (Towbin et al 1979). The lupin exffact was separated as before on a l% agarose gel and the proteins were ffansferred to nitrocellulose paper.…”
Section: Mots Cl6s: Lupin Conglutine Anticorps Polyclonalmentioning
confidence: 99%
“…Heated soyabean flour is the most widely used legume protein in monogastric feeding. However, it has been shown to cause immunological reactions in preruminant calves, which in severe cases can lead to alteration of the intestinal morphology of sensitized animals (Barratt et al, 1978;Kilshaw, 1981; Seegraber and Morrill, 1986 Bush et al, 1992). Thus the exploration of other temperate-growing legumes, such as lupins, becomes of interest particularly because of their high content of protein in the seed, which compares favorably with that of soyabean, and in some species is highest among legumes (Cerletti, 1993 (Hudson, 1979 (table I) and an 80% decrease in soluble sugars (data not shown), compared to those found in defatted soyabean (Lailbs et al, 1994) and lupin (Hudson, 1979;INRA, 1984) (Heppell et al, 1987) (Guilloteau et al, 1986).…”
Section: Introductionmentioning
confidence: 99%